Organic and inorganic model soil fractions instigate the formation of distinct microbial biofilms for enhanced biodegradation of benzo[a]pyrene - Han, Cheng; Zhang, Yinping; Redmile-Gordon, Marc; Deng, Huan; Gu, Zhenggui; Zhao, Qiguo; Wang, Fang (Journal of hazardous materials, 2021)
This study conducted the sorption and biodegradation of benzo[a]pyrene (BaP) by microbial biofilm communities developed on proxies for materials typically found in soils. The half-life of BaP was 4.7 and 2.3 weeks for biofilms on the inorganic carrier (BCINOR, montmorillonite) and on the organic carrier (BCOR, humic acid), respectively. In contrast, the half-life was 7.0 weeks for specialized planktonic cultures (PK). The exposure to BaP caused the development of lipid inclusion bodies inside the bacteria of the PK systems and biofilms of the BCINOR, but not on the biofilms of the BCOR system. Interestingly, the BCOR displayed not only the greatest BaP sorption capacity but also the greatest bacterial density and membrane integrity and the shortest bacteria-to-bacteria distances, which were consistent with the increased production of cell surface extracellular polymeric substances on the BCOR. Both carriers caused a noticeable shift in the bacterial genera during the biodegradation of the BaP. The BCINOR selected for Rhodococcus, Brucella, Chitinophaga, and Labrys, whereas the BCOR favored Rhodococcus and Dokdonella. It indicated that ultra-structure and BaP degradation within the organic carrier-attached biofilms differed from the inorganic ones, and suggested that the microstructural heterogeneity and microbial biodiversity from biofilms on the organic carrier promoted biodegradation. [Display omitted] •Biofilms developed on the organic carrier accelerated degradation of BaP.•Cells in biofilms on inorganic carriers formed lipid inclusions.•Biofilms formed on the organic carrier were compact, and featured more EPS.•Gammaproteobacteria and Actinobacteria were linked with the degradation of BaP.